Mass Balance of Hydrocarbons Fuel from Waste Cooking Oil and Plastic by Co-Pyrolysis - Fajar H. Limbong; Delphy Y. A. Praja; Ardika Nurmawati; Ika N. Puspitawati; Erwan A. Saputro (Jurnal Akademika Kimia, 2025)
Indonesia has committed to climate change mitigation through a sustainable energy transition. Currently, the share of renewable energy in Indonesia’s energy mix only reaches 12 %. One type of renewable energy that the Indonesian government is focusing on is biofuel to reduce consumption and dependence on fossil fuels. Bio-oil produced through pyrolysis has the potential to be used as a biofuel. The chosen pyrolysis process is Co-Pyrolysis, which involves two or more feedstocks. In this study, the process was carried out using waste cooking oil (WCO) and HDPE waste as feedstocks. The process was conducted at 450°C for 30 minutes, with varying masses of both feedstocks. The data obtained were analyzed using mass balance and yield analysis to determine the optimal conditions for producing bio-oil as a hydrocarbon fuel. The optimal condition was found at a mass ratio of HDPE: WCO = 1:4, with a bio-oil yield of 78%. Under these optimal conditions, the conversion of HDPE plastic into heptadecane was 29.39%, and the conversion of oleic acid in waste cooking oil into heptadecane was 38.8%. This also serves as an initial step toward developing a pilot plant-scale process using HDPE plastic waste and waste cooking oil.